Myoepithelial carcinoma of lacrimal gland in HIV patient: A rare case - L.P. Suryantini Septia Dewi; Putu Yuliawati; made laksmiNi Made Laksmi Utari; sukartiniA.A.A. Sukartini Djelantik (DiscoverSys Inc., 2022)
Introduction: Lacrimal gland tumors have 1: 1,000,000 cases per year, accounting for one-fourth of lesions that occupy the orbital space. The rarity of lacrimal gland tumors and the many types of tumors with various types of lesions make determining optimal treatment difficult. A myoepithelial tumor is a rare epithelial neoplasm of the lacrimal gland. This paper aims to report a good outcome case of myoepithelial carcinoma. Case Report: A 30-year-old male complained of protruding his left eye since 2014, accompanied by pain and clear white discharge. The vision was getting blurry and also double vision. Patients with Human Immunodeficiency Virus (HIV) disease since 2013 on Anti Retro Viral (ARV) therapy. Right eye visual acuity was 6 / 7.5, and good eyeball examination. The left eye was 6/10 with no pinhole improvement, non-axial proptosis, and superolateral mass. The movement of his left eye was restricted. Other anterior and posterior segments were promising. The patient was diagnosed with pseudotumor and was given oral methylprednisolone. The eye condition is said to be getting better. The patient complained that the left eye was more prominent and protruding three years later, with blurred vision accompanied by infection. Left eye visual acuity becomes Light Perception Bad Projection with non-axial proptosis, retraction of palpebra and pus. Orbital exenteration was performed, and anatomical pathology examination revealed myoepithelial carcinoma of the lacrimal gland. The patient was planned for radiotherapy. Conclusion: These rare cases have made setting up a regimen in randomized controlled trials difficult. The rapid development of therapy gives more hope to treating patients with lacrimal gland tumors.